Double Antithrombotic versus Triple Antithrombotic Therapy in Patients with Atrial Fibrillation and Acute Coronary Syndrome - Dharma, Surya (International Journal of Angiology, 2020)
In atrial fibrillation (AF), oral anticoagulant (OAC) therapy with either vitamin K antagonist or non–vitamin K antagonist is used to prevent thromboembolic complications. In patients who presented with acute coronary syndrome (ACS) and were treated by percutaneous coronary intervention (PCI), dual antiplatelet therapy (DAPT) with aspirin and a P2Y12 inhibitor reduces major adverse cardiac events (MACEs) and stent thrombosis. Consequently, in patients with AF who presented with ACS and were treated by PCI, the combination of OAC and DAPT, the so-called triple antithrombotic therapy (TAT) is needed to improve the outcome of the patients. However, the use of TAT increases the risk of bleeding. Several randomized clinical trials and a meta-analysis evaluated the use of TAT and double antithrombotic therapy (DAT) in this population, and DAT is defined as patients who receive combination of one antiplatelet and OAC. In general, the studies demonstrated a reduction in bleeding event in patients who received DAT as compared with TAT, with similar incidence of thromboembolic complications and MACE. To date, there is no established consensus or guideline for the most appropriate combination of antithrombotic agents in patients with AF and ACS who undergo PCI. Tailoring the treatment for each individual is likely the best approach to determine the balance of bleeding risk and ischemic events before starting antithrombotic therapy. Future trials with adequate sample size are needed to find the most appropriate combination of antiplatelet and OAC in patients with AF who presented with ACS and treated by PCI.
Keywords: atrial fibrillation; acute coronary syndrome; double antithrombotic; triple antithrombotic; bleeding risk